ANALISIS PEMBIAYAAN DAN KREDIT SEKTOR PERDAGANGAN, HOTEL DAN RESTORAN DI INDONESIA - BAHRINA ALMAS (Universitas Islam Negeri Imam Bonjol Padang, 2018)
The purpose of this study was to analyze the factors that influence the financing and credit of the trade, hotel and restaurant sector in Sharia and conventional banking in Indonesia using the Vector Autoregression / Vector Error Correction Model (VAR / VECM) model with monthly data for the period of January 2008 to December 2016. The results show that the factors that influence the financing and credit of the trade, hotel and restaurant sector (PHR) in Sharia and conventional banking, namely Third Party Funds (DPK), Industrial Production Index (IPI), Inflation (INF), Bonus of Bank Indonesia Syariah Certificate (BSBIS), Loan Interest Rate (SBK), Equivalent Rate Financing (ERP) percentage of Non Performing Financing (NPF), percentage of Non-Performing Loans (NPL).